Aesop's Fables - Woollard, Elli (UK, 2019)
Aesop's Fables are enduring classics that are known and loved around the world. This collection of eight beloved stories is delightfully retold in rhyme by the author.
Keywords: Fables; Juvenile Literature; Tales